Hunting for High-mass X-Ray Binaries in the Galactic Center with NuSTAR - Shifra Mandel; Julian Gerber; Kaya Mori; Ceaser Stringfield; Mabel Peñaherrera; Charles J. Hailey; Alan Du; Jonathan Grindlay; JaeSub Hong; Gabriele Ponti; John A. Tomsick; Maureen van den Berg (The Astrophysical Journal)
The central 2 × 0.8 deg ^2 region of our Galaxy contains ∼10,000 X-ray point sources that were detected by a series of Chandra observations over the last two decades. However, the limited bandpass of Chandra below 8 keV hampered their spectroscopic classification. In 2016, the initial NuSTAR Galactic center (GC) survey detected 77 X-ray sources above 10 keV. The hard X-ray detections indicate magnetic cataclysmic variables, low-mass X-ray binaries, high-mass X-ray binaries (HMXBs), or even pulsars. The possibility of HMXB detections is particularly interesting given the dearth of identified HMXBs in the GC. We conducted a search for bright ( K _s  ≲ 16 mag) near-infrared (NIR) counterparts to the hard X-ray sources—utilizing their Chandra positions—in order to identify HMXB candidates. We identified seven NuSTAR sources with NIR counterpart candidates whose magnitudes are consistent with HMXBs at the GC. We assessed the likelihood of random association for these seven sources, and determined that two have a nonrandom association with a probability exceeding 99.98%, making them strong HMXB candidates. We analyzed broadband NuSTAR, Chandra, and XMM-Newton spectral data for these two candidates, one of which was previously identified as a red supergiant. We find that the X-ray spectra are consistent with HMXBs. If confirmed through follow-up NIR spectroscopic studies, our findings will open a new window into our understanding of the intrinsic luminosity distribution of HMXBs in our Galaxy in general and the GC HMXB population in particular.